2018
DOI: 10.1177/0284185118813599
|View full text |Cite
|
Sign up to set email alerts
|

Application of whole-lesion intravoxel incoherent motion analysis using iZOOM DWI to differentiate malignant from benign thyroid nodules

Abstract: Background Intravoxel incoherent motion (IVIM) parameters derived from iZOOM diffusion-weighted imaging (DWI) can be used to quantitatively identify malignant thyroid nodules. However, the criteria are not standardized. Purpose To determine IVIM parameter values derived from iZOOM DWI that can differentiate malignant from benign thyroid nodules. Material and Methods Forty-two patients with 46 pathologically confirmed thyroid nodules. All patients underwent preoperative examinations with conventional and iZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…D* reflects the contribution of perfusion to signal attenuation of the diffusion image (20). It has been reported that the D* value may be unreliable in the IVIM model for differential diagnosis and has poor measurement reproducibility (21). DKI is a non-Gaussian diffusion weighted analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…D* reflects the contribution of perfusion to signal attenuation of the diffusion image (20). It has been reported that the D* value may be unreliable in the IVIM model for differential diagnosis and has poor measurement reproducibility (21). DKI is a non-Gaussian diffusion weighted analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…But in clinical circumstances, ss-EPI DWI of optic nerve suffers from partial-volume effects, magnetic susceptibility artifacts, chemical shift artifacts, and low image quality on account of the small dimension of the nerves and low resolution [ 8 ]. Recent studies have indicated that reduced field-of-view (rFOV) DWI provides outstanding improvements in image quality of the spinal cord [ 9 , 10 ], pancreas [ 11 ], prostate [ 12 , 13 ], breast [ 14 ], thyroid nodules [ 15 ], and optic nerve [ 16 ]. Literature has demonstrated that rFOV DWI showed an improvement in subjective image quality for optic nerve in the intraorbital segment compared with ss-EPI [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DWI signal varies with the magnetic gradient‐induced movement of water molecules within a tissue, which is a function of microstructural properties of the tissue such as cellular density and membrane integrity. Some studies have explored the role of DWI in differentiating malignant and benign thyroid nodules 20–24 . Moreover, there is recent evidence that the DWI‐based estimate of tissue average diffusivity, that is, the apparent diffusion coefficient (ADC), can be used to predict thyroid carcinoma aggressiveness 21 .…”
Section: Introductionmentioning
confidence: 99%